Compensatory growth in female Nubian goats in Sudan effect on carcass characteristics, external body measurements and non carcass components (B) - Yagoub, Yagoub Magboul; Babiker, Salih Ahmed (Journal of agricultural, environmental and veterinary sciences, 2025)
Two groups of female goat kids less than one year in age, Nubian ecotype (15 kids/ group) and of the same initial weight (16.5 kg/kid) were subjected to two dietary levels of energy for 105 days, the first group was offered the highest energy diet (11.5 Mj ME/kcl) while the second group was given the lowest dietary energy diet (8.5 Mj ME/kcl). Through this term of the experiment (105 days) kids of the second group were found just to maintain their weight. Then seven kids from the second group was offered the highest energy diet (11.5 MjME/kcl) to reach the final weight obtained by the first group, it spent 175 days to reach that weight. Six kids from each group were selected randomly and slaughtered to study the effect of compensatory growth on carcass characteristics, external body measurements, non-carcass components and meat quality attributes. Carcass characteristics were not affected by compensatory growth. Carcass fat, bone and muscles were increased in the compensating group. Gut fill was slightly decreased in the compensated group. However, dressing percentage increased significantly (P< 0.05) in the compensated group. However Compensatory growth did not significantly affect fat distribution throughout the body, but total body, carcass and visceral fat were increased in the compensating group. All non carcass components were not affected by the compensatory growth except the liver which was significantly (P< 0.05) increased and the udder which was significantly (P< 0.05) decreased in the compensated group. Meat chemical composition was significantly affected by compensatory growth. Percentages of fat, sacroplasmic and Myofibrillar proteins increased significantly (P< 0.01) in the meat from the compensating goats. Moisture, ash, non-protein nitrogen percentages and pH values decreased but not significantly so in the meat from the compensated goat group. Meat from the compensated goat group showed superior water holding capacity and less cooking loss value. Meat from goats that experienced compensatory growth was significantly lighter in colour possibly due to increased fatness. However, redness values of the meat, though not significant .were lower compared with that from normally growing goat kids. Carcass measurements as heart girth and abdomen circumference were significantly (P< 0.05) increased by the compensatory growth, while measurements, as body length and scapular and thigh circumference were not significantly affected.